Approximate fuzzy analysis of linear structural systems applying intervening variables. (1st January 2016) - Valdebenito, M.A.; Pérez, C.A.; Jensen, H.A.; Beer, M.
Highlights: Linear static structures with fuzzy parameters and fuzzy loading are considered. Structural response represented approximately using intervening variables. A single structural analysis and sensitivity analysis are required. Approach captures nonlinearity of response with respect to uncertain parameters. Abstract: This contribution presents an approach for performing approximate fuzzy structural analysis of linear static systems. The proposed approach is based on an approximate representation of the structural displacement (which is constructed using intervening variables) and is capable of dealing with uncertainty present in both structural parameters and loading. The most salient features of the proposed approach are its capability of capturing the nonlinearity of the structural response with respect to uncertain parameters and its numerical efficiency.